Enhanced drug delivery in cancer therapy: role of TMPRSS4 protease in liposomal engineering - Kim, Ji Hoon; Kwak, Jeong Hun; Choi, Ho Joong; Lee, Dosang; Park, Jung Hyun; Kim, Ok-Hee; Kim, Say-June (Biotechnology and bioprocess engineering, 2025)
This research centers on leveraging the proteolytic activity of TMPRSS4 (transmembrane protease, serine 4), a transmembrane protease frequently found on tumor cell membranes, for the development of anticancer therapeutics. A novel liposome design was developed, incorporating transmembrane peptides (TMPRSS4-cleavable peptides; TCPs) on the surface that are selectively degradable by TMPRSS4, aimed at improving intracellular delivery efficiency. The efficacy of TCP-liposomes (TCP-L) in targeting tumor cells and delivering cargo was evaluated in comparison to control liposomes (CL). The liposomes were manufactured using a microfluidic technique, where TCPs were attached via sonication, and doxorubicin (DOX) was encapsulated as necessary. To compare the efficiency of intracellular cargo delivery, the fabricated liposomes were tested across various cancer cell lines and in an in vivo xenograft model of gastric cancer. In vitro studies showed DOX TCP-L significantly enhanced doxorubicin release in lung, colon, gastric, and pancreatic cancer cell lines compared to DOX CL ( P < 0.05). In vivo experiments using the gastric cancer xenograft model demonstrated the highest Total Radiant Efficiency (TRE) in the 100 μg DOX TCP-L group ( P < 0.05), followed by 50 μg DOX TCP-L, 100 μg DOX CL, and 50 μg DOX CL. Immunohistochemical staining of excised xenograft tumor tissues revealed an increase in the pro-apoptotic marker Bax and a decrease in the anti-apoptotic marker Mcl-1 in the DOX TCP-L group compared to the DOX CL group. The findings suggest that TCP-L enhance intracellular cargo delivery, likely due to TMPRSS4-induced liposomal destabilization in cancer cells, showcasing the potential of TCP-L for improved drug delivery in cancer treatment.